Rancang Bangun Sistem Informasi Monitoring Santri Berbasis Progressive Web App (PWA) Pada Pondok Pesantren Al-Fatich Surabaya - Khoirul Ansori; Dwi Fatriyanto Suyatno (CV. SINAR HOWUHOWU, 2026)
Monitoring of santri (students) development at Pondok Pesantren Al-Fatich Surabaya still relies on a manual instrument called the “Buku Kepribadian Santri” (Student Personality Book), which records attendance, discipline, permits, and health. Reports are compiled and delivered to parents/guardians (wali santri) only once a month, causing delayed information, limited real-time access, risk of losing physical archives, and inefficient recap processes for pondok administrators. A pre-survey of 21 resident guardians found that 85.7% had felt anxious because they could not monitor their child's condition in real time, while 100% already used Android smartphones and 81% were willing to use a Progressive Web App (PWA)-based monitoring application. This study aims to design and build a santri monitoring information system based on Progressive Web App (PWA) chosen for its installation-free access and reliability under the limited network and device conditions common in pesantren environments that digitizes the Student Personality Book by integrating Attendance, Permit, Discipline, and Health modules into a single, real-time platform. The system, named SIMALFA, was developed using the Rapid Application Development (RAD) method through Requirements Planning, Design Workshop, and Implementation phases, built with React.js, Node.js, Express.js, and MySQL, and supported by PWA capabilities such as Service Worker caching, IndexedDB, background sync, and push notification so that it remains usable under limited network conditions. Black Box Testing on 88 test scenarios covering all modules showed a 100% success rate, indicating that the system is feasible for implementation. Once deployed, the system is expected to provide guardians with real-time digital reports and push notifications, help administrators automate attendance recap, and reduce reliance on fragile physical records, thereby increasing the transparency and efficiency of santri development monitoring at the pondok.